ANALISIS PENINGKATAN FAKTOR KERJA MOTOR INDUKSI 3 PHASA - Barlian, Taufik; Faroda, Ahmad (JURNAL SURYA ENERGY, 2016)
Following to the rapid indrustry, where many major indrustries using electric motors and other electricalequipment that is inductive, so that the reactive power consumption increase. For indrustrial low power factorcannot be avoided because each motors has variable load. Induction motors with a full load can provide highpower factor, but when the motor is low, its power factor will decrease. Its condition can be overcome by usingcapacitors. Capacitors are mounted paralell to the motor can be used to improve the power factor. The value ofthe capacitors depends on the reactive power generated by the motor. Component reactive power inductiveshould be reduced and the reduction can be done by adding capacitor. The reduction process can occur becausethe load is inductive and capasitive its opposite direction due to its reactive power into a small and show that at22 % load power factor improvment occurs 0.5151 into 0.5174.